2011
DOI: 10.1200/jco.2010.31.8121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pretransplantation Minimal Residual Disease, As Detected by Multiparametric Flow Cytometry, on Outcome of Myeloablative Hematopoietic Cell Transplantation for Acute Myeloid Leukemia

Abstract: These data suggest that pre-HCT MRD is associated with increased risk of relapse and death after myeloablative HCT for AML in first morphologic CR, even after controlling for other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
285
3
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 358 publications
(315 citation statements)
references
References 31 publications
21
285
3
6
Order By: Relevance
“…39 Minimal residual disease detected using up to 10-color multidimensional flow cytometry has been shown to predict relapse in MAC allo-HCT settings in adults or in children. 40,41 Our study did not find that patients with lower blast counts had favorable outcome compared with those with higher blast counts, while still being in morphologic CR. This suggests that the quantity of non-leukemic myeloblasts has no influence on outcome.…”
Section: Discussioncontrasting
confidence: 61%
“…39 Minimal residual disease detected using up to 10-color multidimensional flow cytometry has been shown to predict relapse in MAC allo-HCT settings in adults or in children. 40,41 Our study did not find that patients with lower blast counts had favorable outcome compared with those with higher blast counts, while still being in morphologic CR. This suggests that the quantity of non-leukemic myeloblasts has no influence on outcome.…”
Section: Discussioncontrasting
confidence: 61%
“…2). Walter et al have reported that MPFC detectable MRD prior to HCT is independently associated with relapse after HCT [17]. Since MRD prior to HCT reflects ineffectiveness of chemotherapy prior to HCT these results suggest that ineffective chemotherapy begets ineffective HCT, although the effect pre HCT of a given increment in MPFC detectable MRD seems greater, at least in children, in ALL than in AML [18].…”
Section: Minimal Residual Disease (Mrd)mentioning
confidence: 99%
“…18 The impact of MRD evaluation performed before allogeneic, either related or unrelated hematopoietic stem cell transplantation has been reported in patients with ALL and acute myeloid leukemia and found to be associated with outcomes. 19,20 In order to verify whether MRD determination before the allograft has prognostic significance in patients given UCBT, we conducted a retrospective analysis on children with ALL transplanted from an unrelated cord blood donor and reported to the Eurocord registry.…”
Section: Introductionmentioning
confidence: 99%